GAMBARAN PERILAKU MENYUSUI EKSKLUSIF PADA IBU BEKERJA - Zafira ' '; Oswati ' Hasanah; Siti Rahmalia ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this research was to describe behavior working mother’s exclusive breastfeeding behavior. The design of this research was  descriptive and conducted on working mother’s in Puskesmas Melur working area. 62 who were taken by using purposive sampling techniques. Measuring instrument used were questionnaires that have been tested for validity and realibility. Analysis was used univariate in the form of a frequency distribution. The results showed majorly exclusive breastfeeding behavior in working mother’s a less level (56,5%). The results of this research was recommend to every health care to giving health promotion about behavior on breastfeeding in working mother’s. Key words             : Behavior, Breasfeeding, working mother’s Reference              : 35 (2005-2013)